Acute cardiovascular changes in women undergoing in vitro fertilisation (IVF), a systematic review and meta-analysis. (May 2020) - Fujitake, Eri; Jaspal, Raj; Monasta, Lorenzo; Stampalija, Tamara; Lees, Christoph
Abstract: Objectives: Ovarian stimulation during fertility treatment leads to profound maternal physiological changes. Women undergoing in vitro fertilisation (IVF) may be at an increased risk of future cardiovascular morbidity, though little is known about the effects on maternal cardiovascular function. We aim to systematically review whether IVF treatment is associated with changes in maternal haemodynamic parameters, and the effects of different protocols. Study Design: A systematic review and meta-analysis of English language studies identified on Medline and EMBASE database, between 1978, to 2019. Search terms: IVF, maternal haemodynamics, and cardiovascular. Studies reporting on ovulation induction, intrauterine insemination, and oocyte donation were excluded. Methodological quality was assessed by using the adapted Critical Appraisal Skills Programme (CASP) checklist. A meta-analysis was conducted for blood pressure and heart rate on patients undergoing the long GnRH agonist protocol according to Cochrane guidelines. We considered four time points in the IVF cycle, in chronological order: pre-treatment, pituitary down regulation, peak oestradiol and the luteal phase. Results: Nine suitable studies were identified; four fulfilled the criteria for meta-analysis. Two studies measuring heart rate found a significant increase in heart rate from pituitary down-regulation to peak estradiol levels, which was supported by the meta-analysis (3.78 ± 2.18 (p= < 0.0001) ). Three studies reported a significant decrease in blood pressure from baseline, with those suitable for meta-analysis showing a significant decrease in mean arterial pressure (-2.08 ± 1.79 (p= < 0.0001) ). Cardiac functional changes were reported for all studies and the changes depended on the type of protocol used. Conclusions: In Vitro Fertilisation leads to acute changes in maternal haemodynamics at different time points of the stimulation protocol. We found an increase in heart rate from pituitary down-regulation to peak estradiol levels and a significant decrease in blood pressure from baseline or pituitary down-regulation to the luteal phase. Cardiac functional changes were reported for all studies on the agonist protocol, but no significant changes were found using the antagonist protocol. It remains unclear as to whether these acute changes were associated with pregnancy complications or chronic cardiovascular sequelae.